A scenario for change: reflective practice for post-ordination professional development. Issue 4 (3rd July 2016) - O'Brien, Graham J.
Abstract: The continuing professional development of ordained ministers is an important concept given the ever-changing nature of ministry and society as a whole. Within such a context, professional development needs to cope with continuous change through reflective practice in order to challenge and renew expertise. The proposed scenario for change seeks to embed reflective practice as the central method for the professional development of ordained ministers, thereby extending reflective practice from training and into the mode of lifelong learning. Components of this approach will include: Intentional reflective practice as the central methodology. Communities of practice as the central location for reflective practice. Facilitation as the central mechanism for reflective practice.